2020
DOI: 10.1177/1948550619893961
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Educational Aspirations and Expectations From Adolescence to Young Adulthood: A Longitudinal Study of Mexican-Origin Youth

Abstract: Mexican-origin youth are at increased risk for school dropout and low educational attainment. High educational aspirations and expectations provide a potential source of resilience, given their association with positive educational outcomes. Using data from a longitudinal study of 674 Mexican-origin youth, we examined the development of educational aspirations ("how far would you like to go in school?") and expectations ("how far do you actually expect to go?") from 7th grade ( M age = 12.8) to 2 years post–hi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Educational expectations (i.e., the level of education a person expects to attain) play an essential role in setting goals for the future and act as motivational forces that propel students to pursue higher educational levels (Lawson et al., 2020 ). Educational expectations predict students’ grades as well as their actual educational attainment (Boxer et al., 2011 ; Cunningham et al., 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Educational expectations (i.e., the level of education a person expects to attain) play an essential role in setting goals for the future and act as motivational forces that propel students to pursue higher educational levels (Lawson et al., 2020 ). Educational expectations predict students’ grades as well as their actual educational attainment (Boxer et al., 2011 ; Cunningham et al., 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…In most developing nations, the socioeconomic position has been shown to be a reliable indicator of school dropout Lawrence & Adebowale, 2023). For instance, several studies in African nations have shown that students decide to leave school because of their family's economic status Bzour et al, 2022;Koslouski et al, 2022;Lawson et al, 2020;Nash et al, 2019;. The education of the parents and parents' engagement in their children's education influenced the tendency of dropouts .…”
Section: Family-relatedmentioning
confidence: 99%
“…For Mexican-origin and other Latinx youth, adolescence includes the added features of balancing competing cultural systems to develop, practice, and embody an ethnic–racial identity (Constantine & Sue, 2006). Despite the predominant focus on risks and deficits in studies detailing how this additional pressure may contribute to challenges and problems (Kuperminc et al, 2009), the majority of Mexican-origin youth navigate adolescence successfully and report high levels of life satisfaction, career and educational aspirations, and future-oriented optimism (Azmitia, 2021; Lawson et al, 2020). Theories incorporating broader asset- and resilience-based frameworks have proposed that cultural orientation and ethnic/racial identity processes may intrinsically underlie the positive psychosocial adjustment demonstrated by Mexican-origin youth (Lawson et al, 2020; Rew et al, 2015).…”
Section: Latinx Youth Developmentmentioning
confidence: 99%
“…Despite the predominant focus on risks and deficits in studies detailing how this additional pressure may contribute to challenges and problems (Kuperminc et al, 2009), the majority of Mexican-origin youth navigate adolescence successfully and report high levels of life satisfaction, career and educational aspirations, and future-oriented optimism (Azmitia, 2021; Lawson et al, 2020). Theories incorporating broader asset- and resilience-based frameworks have proposed that cultural orientation and ethnic/racial identity processes may intrinsically underlie the positive psychosocial adjustment demonstrated by Mexican-origin youth (Lawson et al, 2020; Rew et al, 2015). As such, the cultural context experienced by Mexican-origin youth may act as a conduit for PYD, positively influencing their developing sense of self, increasing their self-confidence, competence, and connection to others, and consequently improving their life trajectory.…”
Section: Latinx Youth Developmentmentioning
confidence: 99%